The Relationship between work pressure and job satisfaction among public relations employees in Jordanian universities - Al-Basayeh, Sakhr Abed Rabbo Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aimed to identify the relationship between work pressure and job satisfaction among public relations employees in Jordanian universities. "To achieve the objective of the study, a random sample of (117) public relations employees in Jordanian universities was selected. The researcher prepared a questionnaire consisting of (34) paragraphs divided into two domains (work pressure and job satisfaction). After verifying the validity of the tool and its stability, it was applied to the sample. The results showed that the level of work pressure was high. The results also indicated that the level of job satisfaction was moderate, more over the results showed that there is no significant difference between work pressure and job satisfaction, In light of these results, the researcher recommended the need to alleviate the pressure on public relations employees through Increase the number of employees in the public relations unit and the need to increase incentives and rewards for public relations staff to improve their level of job satisfaction.